Kepemimpinan Kristen Sejati dan Tantangan Generasi Z: Transformasi Nilai, Spiritualitas, dan Keteladanan di Abad 21 - Juwita, Mutiara (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2026)
This article aims to examine the essence of true Christian leadership in facing the challenges of Generation Z through the transformation of values, spirituality, and exemplary living in the 21st century. This study uses a literature review method by examining various theological sources, Christian leadership studies, and contemporary studies regarding the characteristics of Generation Z. The results of the study show that true Christian leadership does not only focus on authority and influence, but also on exemplary living, servant leadership, empathy, integrity, and contextual spiritual mentoring. Generation Z needs leader figures who are authentic, relational, and able to present Christian values relevantly amid digital culture and changing times. Therefore, 21st-century Christian leadership is called to become a means of transformation that nurtures the faith, character, and spirituality of Generation Z so that they are able to live resiliently, reflectively, and rooted in the example of Christ.